Challenges and Solutions in Maharah Kalam Learning: A Qualitative Study in an Islamic Junior High School in Sidoarjo, Indonesia - Islamiyati, Dian; Ammar, Farikh Marzuki (Indonesian Journal of Islamic Studies, 2023)
This study aimed to investigate the challenges faced by students in Maharah Kalam (Arabic speaking skills) learning and the solutions implemented in an Islamic junior high school in Sidoarjo, Indonesia. The research employed a qualitative approach, using observation, interviews, and documentation as data collection techniques. The participants included Arabic language teachers and eighth-grade students. The findings revealed that Maharah Kalam learning comprised three stages: planning, implementation through group-based conversation practice, and evaluation. The difficulties experienced by students were attributed to linguistic factors, such as pronunciation, sentence structure, and vocabulary, as well as non-linguistic factors, including students' educational background, environment, lack of interest, and limited parental support. To address these challenges, the school introduced the mandatory BTQ (Baca Tulis Quran) activity outside regular lessons. This research contributes to the understanding of Maharah Kalam learning in the context of an Islamic junior high school and provides insights into the factors affecting students' Arabic speaking skills. Further research could explore additional strategies to enhance Maharah Kalam learning and consider the influence of motivation, learning environment, and technological integration. Highlight: Importance of Maharah Kalam in Arabic language learning. Factors influencing difficulties in Maharah Kalam learning: linguistic and non-linguistic. Implementation of BTQ activities as a solution to address challenges in Maharah Kalam learning. Keyword: Maharah Kalam, Arabic Language Learning, Challenges, Solutions, Qualitative Research